Study on Biochemical Responses of Nutrient Microalgae Spirulina Platensis and Haematococcus Pluvialis to Zinc Oxide Nanoparticles - Sinouvassane, Djearamane (2019)
Zinc oxide nanoparticle (ZnO NP) is widely used in industrial and personal care products. The massive usage of this nanoparticle has created residues that can cause contamination to the environment. The presence of ZnO NPs in the aquatic environment could lead to accumulation of nanoparticles in aquatic organisms and cause cytotoxic effects. Thus, the present study has investigated the cellular accumulation and the cytotoxic effects of ZnO NPs in nutrient microalgae Spirulina platensis and Haematococcus pluvialis. The microalgal cells were exposed to the various concentrations of ZnO NPs (10 to 200 mg/L) from 6 to 96 h to explore the dose- and time-dependent cellular accumulation and the corresponding cytotoxic effects. Scanning electron microscopy -X-ray energy dispersive spectroscopy (SEM EDX) analysis evidenced the cellular accumulation of zinc in the algal biomass. Quantification of cell associated zinc by inductively coupled plasma optical emission spectroscopy (ICP OES) reported a substantial accumulation of zinc in both microalgae with higher zinc accumulation in S. platensis. Cytotoxicity and oxidative stress assessment results revealed a typical concentration- and time-dependent increase in reactive oxygen species and lipid peroxidation levels and the corresponding decrease in cell viability, biomass and photosynthetic pigments on both microalgae. The study reported 13.97 mg/L of ZnO NPs as 96 h EC50 for S. platensis and 186.67 mg/L of ZnO NPs for H. pluvialis. The microscopic examinations of the algal cells that are interacting with ZnO NPs showed severe cell membrane and intracellular damages. Overall, the present study reported the accumulation of considerable amount of ZnO NPs in algal cells and the corresponding oxidative stress and cytotoxicity in both microalgae. Notably, 96 h EC50 results of the present study reported nearly 13 times higher sensitivity of S. platensis to ZnO NPs’ toxicity compared to H. pluvialis. Hence, the study suggests that S. platensis could be potentially used as a bioindicator for identifying the contamination of ZnO NPs in the nutrient microalgae and also for testing the toxic effects of ZnO NPs on the aquatic organisms.